2012
DOI: 10.7589/0090-3558-48.2.449
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycoplasma ovipneumoniae and M. arginini in Bighorn Sheep Using Enrichment Culture Coupled with Genus- and Species-Specific Polymerase Chain Reaction

Abstract: ABSTRACT:Mycoplasma species are of interest as possible primary pathogens in the pneumonia complex of bighorn sheep (Ovis canadensis). Previous investigations have not commonly detected low frequencies of Mycoplasma spp. from free-ranging bighorn sheep, possibly due to the fastidious and slow growth of these organisms. We developed a culture protocol that employed an average initial 3-day enrichment culture in liquid Hayflick broth in a CO 2 -enhanced atmosphere. The broth was plated to solid Hayflick medium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…data). Furthermore, Weiser et al (2012) found 50% of healthy bighorns tested were positive for M. ovipneumoniae in the nasopharynx. Their finding is supported by the detection of the presence and shedding of M. ovipneumoniae in healthy bighorns in a Colorado herd (L. Wolfe, Colorado Division of Wildlife, pers.…”
Section: Discussionmentioning
confidence: 97%
“…data). Furthermore, Weiser et al (2012) found 50% of healthy bighorns tested were positive for M. ovipneumoniae in the nasopharynx. Their finding is supported by the detection of the presence and shedding of M. ovipneumoniae in healthy bighorns in a Colorado herd (L. Wolfe, Colorado Division of Wildlife, pers.…”
Section: Discussionmentioning
confidence: 97%
“…Mycoplasmas are identified by biochemical and serological testing (Erdağ and Türkaslan 1989; Stalheim 1985; Giangaspero et al 2012). Even though cultures are used for diagnosis in most cases, they are cumbersome and need a long time (Lin et al 2008; Weiser et al 2012). The most recent and rapid molecular methods to identify mycoplasmas are 16S rDNA PCR and denaturing gradient gel electrophoresis (McAuliffe et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…While no defined pathology has been associated with infection with M. arginini, reports from some experimental infections and diagnostic investigations have suggested that M. arginini may play a role in atypical pneumonia of ruminants (Foggie and Angus, 1972;Goltz et al, 1986;Nicholas et al, 2008;Weiser et al, 2012). However, the inability to establish its pathogenic role and its ubiquitous presence has led to the general assumption that M. arginini is a commensal of small ruminants.…”
Section: Between and Within Herd Diversitymentioning
confidence: 94%
“…In order to confirm the species identity of the isolates, a PCR targeting the 16S rRNA of Mycoplasma species was performed on all samples using the primers GPO3 (5' -GGG AGC AAA CAG GAT TAG ATA CCC T -3') and MGSO (5'-TGC ACC ATC TGT CAC TCT GTT AAC CTC -3') (van Kuppeveld et al, 1992). This was followed by a M. arginini-specific PCR using the primers MAGF (5'-GCA TGG AAT CGC ATG ATT CCT-3') and GP4R (5'-GGT GTT CTT CCT TAT ATC TAC GC-3') as described previously (Weiser et al, 2012). DNA sequencing of the 16S rRNA PCR product was performed on a selected set of isolates to confirm the specificity of the PCR assay for species identification.…”
Section: Bacterial Isolates Dna Extraction and Species Identificationmentioning
confidence: 99%
See 1 more Smart Citation